Health Care Supply Chaın and Challenges ın Post Covıd-19 Era - Mr. M. Vasudevarao (International Journal of Advanced Science and Technology, 2020)
The Covid-19 pandemic is a rapidly changing global health disaster that will require exclusive utilization of health care resources that expect will have an impact on our health care services. Currently, each state in India has similar priorities adding new beds, raising the ability of intensive care units, requisitioning portions of private hospitals, ordering lifesaving ventilators, hiring contract medical practitioners, considering in on increasing retirement doctors and nurses services and handover particular government hospitals to Covid-19 positive patients. Supply chain covers all manufacturing, raw material procurement, distribution, storage and warehousing and transport related activities. The Indian pharmaceutical industry faces significant challenges when it comes to transporting ancillary supplies such as bottles and cap, as they do not fall under the category of essential services exempted from the current nationwide lockdown. Government ban on public transportation making it challenging labor to reach manufacturing units. Ancillary goods for medicine production being detained or shut down. This paper explore the impact of health care supply chain post Covid-19 situation. Also, explore the critical position facing by the hospitals, pharma sector and the entire health care sector due to Covid-19 pandemic